Automated airing systems for air quality control in industries and work areas that involve food - Castillo Picado, Gerald (2024)
Automated air control systems for industry are advanced technologies that allow the management and control of air quality in industrial environments, which can sometimes be very heavy due to different aspects of the environment. These systems are made up of sensors, controllers and intelligent software that will allow decisions to be made automatically, they are special for measuring air quality, the amount of humidity, regulating the temperature of the place and avoiding the presence of insects, these Systems have multiple advantages, such as improving the health, comfort and safety of workers, doing this automatically generates a reduction in energy costs and the efficiency of production processes, in addition, they can be customized to adapt to the specific needs of each industry, being a very important point for a good development of the health, environmental and comfort process.